Multilingualism in translations of the EU – the case law of Court of Justice of the European Union in the interdisciplinary perspective - Kozłowska, Joanna (Specialized Languages in Intercultural Communication, 2020)
Multilingualism has been considered one of the most crucial features of the European Union. The constant development of that international organisation calls for a new perspective on the legal translation in the European Union. It is argued that the distinctive nature of the EU translation should be regarded as a reason for o separating it from the theory of legal translation. It is also suggested that the EU translation should be approached from the interdisciplinary perspective as it may provide a broader field of research. Furthermore, such perspective may contribute to a better understanding of the influence of language on the development of the EU case law and it may lead to a better recognition of linguistic precedents in the judgements of the Court of Justice of the European Union.